Quantitative Assessment of the Motor–Sensory Specificity of the Motor and Primary Sensory Neurons after the End-to-Side Neurorrhaphy - Yu, Qing; Chen, Chengwang; Zhang, Xiaolei; lv, Lei; Lin, Kang; Chi, Yonglong; Gao, Weiyang (Journal of Reconstructive Microsurgery, 2013)
We sought to evaluate the motor–sensory specificity of the motor and primary sensory neurons after the end-to-side neurorrhaphy. We divided 90 rats into three groups: (1) end-to-side neurorrhaphy using the ulnar nerve as donor nerve and the musculocutaneous nerve as recipient nerve; (2) normal control; and (3) transected nerve with the stumps buried. At 5 months, we monitored the grooming test, the electromyographic recordings, the histologic changes in the nerve, and quantitatively evaluated motoneurons and dorsal root ganglion (DRG) neurons following their retrograde labeling by Fluoro-Gold (Sigma, St. Louis, MO) applied to the musculocutaneous nerve and its biceps brachii branch. Grooming and electrophysiological investigations recovered successfully in the end-to-side group. The implanted musculocutaneous nerve contained varying but satisfactory numbers of axons. In the end-to-side group, the proportion of motoneurons for the biceps brachii branch of musculocutaneous nerve was very similar to the musculocutaneous nerve sections proximal to this branch (17.3% ± 2.7% and 21.7% ± 3.7%, respectively), but it did not correspond with the proportion of the biceps brachii branch of musculocutaneous nerve in the normal group (28.3% ± 3.5%). The present study confirms that limited but functional reinnervation can occur after the end-to-side neurorrhaphy, and the motor–sensory specificity is not important.
Keywords: neuron; end-to-side neurorrhaphy; motor–sensory specificity